Beyond Native Standards: A Pedagogical Strategy for Listening Comprehension through Authentic Materials and Accent Awareness - Nadila Mudea N; Sorta Hutahean; Junaidi; Edward; Sunengko; Firmansyah (EJI (English Journal of Indragiri): Studies in Education, Literature, and Linguistics, 2026)
In the context of increasing global use of English, students are now frequently exposed to different accents, although many classrooms still prioritize native-speaker norms that can limit learners’ confidence in listening. This study explores how an English Literature classroom can be reoriented by questioning the dominance of the native-speaker standard and how students’ perceptions shift from viewing accents as “errors” to understanding them as part of real-world communication and identity. This study used a qualitative descriptive design involving thirteen undergraduate students selected through purposive sampling. Data were collected from reflective responses after a structured listening comprehension task using authentic materials such as Singlish interviews and Indian English videos. The data were analyzed using thematic analysis to identify recurring patterns in students’ experiences. The findings show that exposure to diverse accents helps students become more flexible listeners. Instead of focusing on native-like pronunciation, they gradually rely more on context and meaning to understand spoken English. This process also helps reduce listening anxiety when dealing with unfamiliar accents. Drawing on Global Englishes and Intercultural Communicative Competence, this study suggests that listening should be understood as meaning-making in context rather than simply recognizing ideal pronunciation. It also highlights the importance of valuing linguistic diversity in English as a global language.